General Theoretical Aspects of Legal Development - KRYZHANOVSKYI, Anatolii; MANKO, Denys; SIERYKH, Olena; ATAMANOVA, Natalia; ZGHAMA, Antonina (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019DO - 10.14505/jarle.v10.7(45).15, 2019)
The processes of globalization (that have taken place over the last decades) have contributed too many transformations in legal processes. The same changes are being followed in legal development. Therefore, it is important to analyze the general theoretical aspects of legal development at the present stage. The purpose of this work is to study the general theoretical aspects of legal development. The object of the study is the general theoretical aspects of legal development. The subject of the study is the public relations that influence legal development, as well as the analysis of patterns and general theoretical aspects of such development. The research methodology consists of general theoretical and special scientific methods, namely: hermeneutic method, system-structural method, structural-functional method, historical-legal method, comparative - legal method, formal-logical methods (analysis and synthesis, induction and deduction, proof and refutation, comparison, generalization). As a result of the research, the general theoretical aspects of legal development are analyzed, the peculiarities of formation and existence of qualitative and quantitative changes in the legal sphere of public life are revealed, reflecting the level of legal development of an individual and community of people, the degree of perfection of forms of their legal communication and interaction.